Pretpostavka nevinosti okrivljenog kao element prava na pravično suđenje - Drago Radulović (Revija za kriminologiju i krivično pravo)
Although the presumption of innocence has its roots in the rational criminal procedure of the ancient times, it should still be seen as a result of the modern criminal procedure system, i.e. the French bourgeois revolution and its first regulation in the 1789 Declaration of the Rights of Man and of the Citizen. It has always been the subject of interest of scientists and experts, and in recent years it has become one of the most popular topics on the legislative, theoretical and practical level. Due to its topicality, the presumption of innocence is the subject of this paper. In addition to the introductory notes, explaining the importance of this principle for the defendant, the paper also covers the definition of the presumption of innocence in international legal documents and national legislation, followed by different understandings about the legal nature and content of the presumption of innocence. Furthermore, the paper then analyses the presumption of innocence as an element of the right to a fair trial, which is based on three main pillars – that the defendant is treated without prejudice and bias, that the burden of proof is not on him, and that in case of doubt about the existence of the facts, the court always decides in favour of the defendant. Finally, the paper discusses respect of the presumption of innocence by extrajudicial entities, which is of particular importance for the mass media, where a journalist should morally condemn a criminal offense that exists based on a certain degree of suspicion, but not the person who has just been suspected or accused.